A Methodological Approach to Dematerialization of Business Processes Using Open-Source Technology - Ávila, Liliana; Teixeira, Leonor; Almeida, Pedro (International Journal of Industrial Engineering and Management, 2018)
Projects of dematerialization of business processesalloworganizations to modernize their administrative activities through the rationalization and optimization of information flows and elimination of documents circulating in paper format. In this articleis proposed a methodology for the implementation of projectsof dematerialization of business processesin public and private organizations constituted by four stages: preliminary studies and requirements elicitation, modelling, construction and transition. It is also describeda pilot-experience in a public entity using an open-source software(Bonita Open Solution) in order to validate the proposed methodology and confirm open-source technologies as a good option to implement this type of projects in a low-cost approach. Furthermore, throughout the paper,some guidelinesare providedbased on critical success factors and tools to support development stages. Article history: Received (22.11.2016); Revised (15.03.2017); Accepted (19.10.2017)